1999
DOI: 10.1366/0003702991945506
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Quantitative Analysis of Steel Composition by Laser-Induced Breakdown Spectroscopy at Atmospheric Pressure Using an Infrared Nd:YAG Laser

Abstract: The experimental conditions and procedure for quantitative analysis of steel by laser-induced breakdown spectroscopy in argon at atmospheric pressure using an infrared Nd:YAG laser have been studied. Satisfactory analytical results have been obtained for the determination of C, Si, Cr, and Ni contents in low-alloyed steels. The lens-to-sample distance is shown to be a relevant parameter, which can be selected at each pulse energy to enhance the line intensities and the repeatability of measurements. A higher p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(68 citation statements)
references
References 18 publications
1
66
0
1
Order By: Relevance
“…[11][12][13][14] Many groups around the globe are working on LIBS quantitative elemental analysis using calibration curve method. [15][16][17][18][19][20] For this, generally, a calibration curve prepared by using the emission line intensity of the analyte material versus its concentration is used. The curves are constructed using known standard elemental concentrations in a matrix matching the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] Many groups around the globe are working on LIBS quantitative elemental analysis using calibration curve method. [15][16][17][18][19][20] For this, generally, a calibration curve prepared by using the emission line intensity of the analyte material versus its concentration is used. The curves are constructed using known standard elemental concentrations in a matrix matching the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Mao et al, 16 Aguilera et al 17 and Aragon et al 18 reported that the experimental conditions which can affect the analytical performance need to be optimized carefully for meaningful quantitative results from the linear calibration curve. Based on the purpose for which LIBS is to be used, one needs to make a judicious choice of the spectrograph, detectors and collection/excitation optics.…”
Section: Introductionmentioning
confidence: 99%
“…In order to correct the matrix effect on the calibration curves, a number of methods have been proposed [15][16][17]. The procedure based on normalization with respect to a reference line can provide higher accuracy and reproducibility of the analytical results than methods using simple line intensity [15].…”
Section: Introductionmentioning
confidence: 99%
“…The procedure based on normalization with respect to a reference line can provide higher accuracy and reproducibility of the analytical results than methods using simple line intensity [15]. Panne et al propose a model which includes the equilibrium Saha and Boltzmann relationships to correct the pulse-to-pulse variability of the plasma electron temperature and density [16].…”
Section: Introductionmentioning
confidence: 99%
“…Számos tanulmány felhívta rá a figyelmet, hogy a plazma fényének térbeli integrálása a jel reprodukálhatósága szempontjából elınyös [pl. 33,36,37], ezért az egy győjtılencsés megoldások sokszor jobb eredmé-nyeket produkálnak, mint a két vagy több győjtılencsés (a plazmát pontszerő objektumként leképezı, képalkotáshoz megfelelı) megoldások.…”
Section: Irodalmi áTtekintés 12 a Libs Készülékek Részeiunclassified